Investigation of shear behaviour of polymer composite golf shaft. (2017) - Vijaya Ramnath, B.; Jeykrishnan, J.; Elanchezhian, C.; Keshavan, D.; Deepak, M.
Abstract: Composite materials have been proven viable for use in manufacturing industries such as aerospace, automotive manufacturing and, sports industries etc. In the field of sports, composite materials play an ever growing important role in improvement and better performance of sports equipments as they have better strength to weight ratio. One such application is that of the golf shaft where the golf shaft is subjected to shear load. Hence, the conventional steel golf shaft may be replaced with polypropylene based polymer composite which reduces the weight and increases the performance of the shaft. The strength and hardness of polypropylene is an important factor for selecting it widely. In this work, the shear behaviour of golf shaft was evaluated to know its shear characteristics. The results of the shear tests seem to fall in the safe line which make the golf shaft most useful for sports applications.